Universal Science : An Introduction to Islamic Metaphysics. - Yazdī, Mahdī Ḥāʼirī. (The Modern Shīʿah Library, 2017)
The Universal Science ( ʿIlm-i kullī ) by Mahdī Ḥāʾirī Yazdī , is a concise, but authoritative, outline of the fundamental discussions in Islamic metaphysics. For many years used as a textbook in Iran, this short text offers English readers a readily accessible, lucid, and yet deeply learned, guide through the Sadrian, Avicennan, and Illuminationist schools of thought, whilst also demonstrating how the 'living tradition' of Shīʿī philosophy engages with central ontological, epistemological, aetiological, and psychological questions. Discussions include the primacy of existence; the proper classifications of quiddity; and the manifold properties of causality and causal explanation. This is the first of the various influential works authored by this leading Shīʿah intellectual to have been translated into English from the original Persian.